2014
DOI: 10.1089/thy.2013.0062
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Differentiated Thyroid Cancer in Relation to Serum Thyrotropin and Thyroglobulin Antibody Status at Time of Diagnosis

Abstract: Preoperative serum TSH level is associated with higher DTC stage, gross extrathyroidal extension, and neck node metastases. Perioperative TgAb is not an independent predictor of DTC prognosis. A larger cohort is required to assess whether preoperative serum TSH level predicts recurrence or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 37 publications
8
75
0
4
Order By: Relevance
“…From 1997-2000 and from 2005-2008, the incidence increased 5.2% per year and was highest among females below age 50 years. PTC was the main histologic type related to the incidence increase, and there was a decrease in other histological types (2).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…From 1997-2000 and from 2005-2008, the incidence increased 5.2% per year and was highest among females below age 50 years. PTC was the main histologic type related to the incidence increase, and there was a decrease in other histological types (2).…”
Section: Introductionmentioning
confidence: 95%
“…The literature reports that less than 5% of patients die from the disease within 10 years. However, poorly differentiated and anaplastic carcinomas have a very poor prognosis, with a mean survival of less than 6 months in the anaplastic cases (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…We were the first to publish that serum TSH is raised in patients with malignant thyroid nodules compared with those with benign disease (Boelaert et al 2006), and subsequent studies have shown that pre-operative serum TSH is proportionally higher in those with more aggressive disease (Boelaert et al 2006, Jonklaas et al 2008, Haymart et al 2009, McLeod et al 2014, Fighera et al 2015. This review aims to explore the relationship between TSH and thyroid cancer, both before and after a diagnosis of malignancy is made.…”
Section: :11mentioning
confidence: 99%
“…They suggest that as Hashimoto's disease often progresses to hypothyroidism resulting in elevated TSH concentrations and because Graves' disease is associated with TSH receptor stimulation, which is associated with thyroid cancer (Mazzaferri 2000), it follows that TSH receptor activation is the link between thyroid cancer and thyroid autoimmune disease. More recently, a study directed at assessment of anti-thyroglobulin antibody (TgAb) measured pre-operative levels in differentiated thyroid cancer patients and concluded that TgAb was not an independent predictor of DTC prognosis, once adjusted for age and gender (McLeod et al 2014). They noted that TgAb may be raised in autoimmunity and in patients exhibiting an immune response to the tumour, and may not be a true representation of thyroid autoimmune disease.…”
Section: Serum Tsh and Thyroid Autoimmunitymentioning
confidence: 99%
“…The data collection and analytical methods of the NTCTCS have been described elsewhere (8,9,(14)(15)(16)(17)(18)(19)(20). Briefly, 11 North American centers contributed patient data, with registration beginning in January 1987 (this data analysis captures patients registered through to 2011).…”
Section: Registry Protocol and Data Collectionmentioning
confidence: 99%